Association between Adverse Childhood Experiences and Internalizing Symptoms in Adults at a Wellness Centre in India - Riri G. Trivedi; Anita Kumar; Kathirvel Soundappan; Gunjan Y. Trivedi; Hemalatha Ramani; Saurabh Kumar (Indian Journal of Community Medicine)
Background: Adverse childhood experiences (ACE or childhood trauma) include very stressful and potentially traumatic events linked to a higher risk of mental health challenges and chronic conditions. India has an opportunity to study the association between ACE exposure and internalizing symptoms (depression and anxiety). To evaluate the association between exposure to ACE and internalizing symptoms (depression and anxiety) at a wellness centre in India. Methods and Material: This cross-sectional study studied a convenience sample of 909 individuals who self-assessed ACE exposure, depression (Major Depression Inventory: MDI), and anxiety levels (Generalized Anxiety Disorder: GAD-7). Logistic regression models evaluated the association between ACE and depression and anxiety levels. Results: The results show a strong association between ACE levels and depression as well as anxiety. Individuals with medium (1-3 ACEs), high (4-6 ACEs), and very high (> =7 ACEs) exposure to childhood trauma are at 2–7 odds of having major depression and 1–3 odds of having anxiety. Moreover, both Gen Z and Gen Y are at a higher risk of depression and anxiety compared with Gen X. Conclusions: The research extends the findings from global research on ACE and mental health (depression, anxiety) in India, highlighting the strong association. Future work should expand the samples across the geography to enhance the insights.